Lay perspectives on the social and psychological functions of heroes - Kinsella, Elaine L.; Ritchie, Timothy D.; Igou, Eric R. (Frontiers in Psychology, 2015)
Declaring and thinking about heroes are common human preoccupations but surprisingly aspects of heroism that reinforce these behaviors are not well understood. In four thematically consistent studies, we attempt to identify lay perspectives about the psychological functions served by heroes. In Study 1, participants (N = 189) freely generated open-ended descriptions of hero functions, which were then sorted by independent coders into 14 categories (e.g., instill hope, guide others). In Study 2, in an attempt to identify the most important functions associated with heroes, participants (N = 249) rated how each function corresponded with their personal views about heroes. Results from a confirmatory factor analysis suggested that a three-factor model of hero functions fit the data well: participants thought that heroes enhanced the lives of others, promoted morals, and protected individuals from threats. In Study 3 (N = 242), participants rated heroes as more likely to fulfill a protecting function than either leaders or role models. In Studies 4a (N = 38) and 4b (N = 102), participants indicated that thinking about a hero (relative to a leader or an acquaintance) during psychological threat fulfilled personal enhancement, moral modelling, and protection needs. In all, these findings provide an empirical basis to spur additional research about the social and psychological functions that heroes offer.